GENDER DIFFERENCES IN LITERACY AND NUMERACY ACHIEVEMENT: A CRITICAL REVIEW - Melyana R Pugu; Aslan Aslan (CV. ADIBA AISHA AMIRA, 2025)
This study addresses gender differences in literacy and numeracy achievement through a critical review of existing literature. The results show that females tend to excel in literacy, while males often do better in numeracy. Factors influencing these differences include gender stereotypes, social support, pedagogical methods, and individual interests and motivation. This study emphasises the importance of a more gender- responsive and inclusive approach to education to reduce this achievement gap. Recommended strategies include equal interest coaching, gender stereotype awareness programmes and active involvement of parents and the school community. This will create a supportive learning environment for all students, thereby improving overall literacy and numeracy achievement.